Some observations on the biology of two rarely seen deep‐sea chimaerids, Chimaera carophila and Hydrolagus homonycteris. Issue 5 (7th March 2017) - Finucci, B.; Stevens, D. W.; Jones, E. G.; Dunn, M. R.
Abstract : Chimaera carophila ( n = 45) and Hydrolagus homonycteris ( n = 11), two deep‐sea chimaerids rarely caught in the waters off New Zealand, were collected from research trawl catches and commercial fishery catches around New Zealand at depths between 400 and 1300 m, between 2014 and 2016. Additional preserved specimens of both species ( n = 58) from museum collections were analysed for size, sex and maturity. External assessment of male claspers and a combination of internal assessments of female gonad mass and oviducal gland width, were used to determine maturity. For both species, length at first maturity was 0·70–0·82 of their maximum observed chimaera length ( L C ), with females maturing at a larger size. Length at maturity for C. carophila ( L C range: 28·7–103·9 cm) was estimated at 72·5 cm L C for males ( n = 163) and 82·5 L C for females ( n = 58). In H. homonycteris, length at maturity (length range: 78·6–99·8 cm L C ) was estimated at 79·1 cm L C for males ( n = 51) and 80·1 cm L C for females ( n = 17). Ovarian fecundity was up to 31 for C. carophila and sperm storage was confirmed in the oviducal gland of this species. Both species preyed on benthic invertebrates. Some C. carophila and H. homonycteris inhabit depths beyond most current fisheries, but both species appear to be relatively rare and have reproductive parameters characteristic of low productivity, which may make these species vulnerable to population decline if mortality was to increase in the future.